The crime of aggression as a violation of the rights of one's own population. (2nd January 2022) - Mégret, Frédéric; Redaelli, Chiara
ABSTRACT: In its traditional understanding, aggression is a crime against state. A number of scholars have, by contrast, increasingly framed the wrong of aggression as lying in its devastating consequences for the populations affected. That emergent human rights framing, however, has largely focused on the population of the other state. This article seeks to go beyond this nascent human rights framing of aggression, by looking at the possibility that waging an illegal war can also be interpreted as a violation of the rights of a state's own population, including both combatants and non-combatants. In doing so, we seek to reconnect the argument against aggression to domestic human rights themes involving the responsibility of the sovereign towards persons within its jurisdiction. We suggest that this approach can help produce a more normatively grounded and textured account of the grounds for proscribing war that better connects both domestic and international legal conversations.